Market risk factors and stock returns in the Nigerian bourse - Omorose A. Ogiemudia; Osagie Osifo; Igbinovia L. Eghosa (CBN Journal of Applied Statistics, 2022)
This study examines the link between market risk and equity return in Nigeria between 1980 to 2019. It employs the vector error correction model (VECM) to determine the short run dynamics and long run effect of market risk factors on stock return. The findings revealed that a dynamic relationship exists between market risk factors and stock returns in Nigeria. Also, exchange rate risk and oil price risks have significant influence on stock return, while inflation and interest rate risk, and political instability risks have a non-significant impact on stock return. Finally, a unidirectional relationship was detected between interest rate, oil price, political instability and stock return. The study concludes that market risk factors of exchange rate, oil price, interest rate and political instability risks are major determinants of stock return in Nigeria. It is recommended that rational investors seeking maximum returns should minimize market risk factors by diversifying their portfolios and study the risk behaviour and level in the market before taking investment decisions.
Keywords: B22; C32; E44; 330; Granger causality; market risk factors; Nigeria; stock return; VECM